2022
DOI: 10.21203/rs.3.rs-2175892/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Network pharmacology to explore the mechanism of scutellarin in the treatment of brain ischemia and experimental verification of JAK2/STAT3 signaling pathway

Abstract: Objective This study elucidated the neuroprotective mechanisms of scutellarin in microglia and astrocytes during the progression of neuropathology in cerebral ischemia. Methods Network pharmacology was first used to filtrate the core targets and pathways. Arising from this, JAK2/STAT3 signaling pathway was specifically identified and experimentally verified. Expression of JAK2/STAT3 signaling related proteins in TNC-1 astrocytes subjected to different treatments with BV-2 microglia conditioned medium (CM) wa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…MENG et al found that scutellarin can treat cerebral ischemia by regulating MARK, phosphatidylinositol 3 kinase (PI3K), hypoxia-inducible factor-1 (HIF-1), and other pathways, thus exerting vasorelaxation, anti-inflammatory and antioxidant effects [ 31 ]. Jia et al [ 32 ] found through network pharmacology and experimental validation that Scutellarin exerts therapeutic effects on cerebral ischemia by activating astrocyte JAK2/STAT3 signaling, which provides a solid experimental basis for its clinical application. Xie et al [ 33 ] found that Scutellarin exhibited antioxidant, anti-inflammatory, and neuroprotective effects in cerebral ischemia/reperfusion injury (CIRI) through PI3K/Akt pathway-mediated Nrf2 activation.…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…MENG et al found that scutellarin can treat cerebral ischemia by regulating MARK, phosphatidylinositol 3 kinase (PI3K), hypoxia-inducible factor-1 (HIF-1), and other pathways, thus exerting vasorelaxation, anti-inflammatory and antioxidant effects [ 31 ]. Jia et al [ 32 ] found through network pharmacology and experimental validation that Scutellarin exerts therapeutic effects on cerebral ischemia by activating astrocyte JAK2/STAT3 signaling, which provides a solid experimental basis for its clinical application. Xie et al [ 33 ] found that Scutellarin exhibited antioxidant, anti-inflammatory, and neuroprotective effects in cerebral ischemia/reperfusion injury (CIRI) through PI3K/Akt pathway-mediated Nrf2 activation.…”
Section: Pharmacological Effectsmentioning
confidence: 99%